Konsep Penguasaan Negara Atas Pemanfaatan Energi Terbarukan Di Laut Indonesia - Br Purba, Marlina (Fakultas Hukum Universitas Surabaya, 2022)
The concept of sovereignty is drawing attention if juxtaposed with the phrase “as big as for the people prosperity”. Therefore the prosperity is for all of the Indonesian people without any exception. What is to be mandated to the country to be sovereignty had and will be used as optimal as possible. If it was not done by the country yet, therefore the phrase “as big as for the people prosperity” is not to be done. This writing is a conceptual article. The analysis mind of economy about the law from utilitarianism Jeremy Betham.